EXERCISE PROMOTION AMONG SCHOOL STUDENTS THROUGH STREET WORKOUT - Yaroshyk, Marta; Bodnar, Ivanna; Malanchuk, Halyna; Rymar, Olga; Solovei, Alla; Semenova, Nataliia; Stefanyshyn, Orest; Stefanyshyn, Nataliia; Petryna, Roman (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2024)
Today in Ukraine, there is a steady trend towards health deterioration of the younger generation. This negative phenomenon is associated with insufficient motor activity of young people (Rymar, Sorokolit, Solovey, Yaroshyk & Khanikiants, 2021; Solovey, Vovkanych, Sorokolit, Rymar, Yaroshyk & Novokshonov, 2021; Yaroshyk, Rymar, Malanchuk, Solovey, Khanikiants & Bubela, 2021). This problem can be solved by developing a positive attitude towards physical exercises, promoting trendy sports. Street workout is popular among young people. This type of activity is safe and suitable for anyone regardless of age, gender and level of physical fitness (Sanchez-Martinez, Plaza, Araneda, Sánchez & Almagiâ, 2017; Taipe-Nasimba &Cantón Chirivella, 2020). Purpose of the article – development of measures to promote physical activity among school students through Street workout. Methods: theoretical analysis and generalization; pedagogical observation; survey; mathematical statistics methods. A redistribution of self-assessed motor activity was recorded among school students at the end of the pedagogical observation after the implementation of the developed measures. Thus, the number of school students whose self-assessment grades were "excellent," "good," and "satisfactory" increased by 19.5%, 10% and 13.4% respectively. There was a 20.2% increase in the number of school students who regularly attended sports clubs. The number of school students who began to engage in physical activity at home increased by 12.8%. The number of school students who started doing morning gymnastics also increased by 13.5%. At the end of the pedagogical observation, the duration of sleep in most school students increased to 7-7.5 hours, and sleep quality improved and reached 6 points.